Typology of Health-Related Behavior: Hierarchical Cluster Analysis Among University Students - Joca Zurc; Matej Majerič (Behavioral Sciences, 2025)
Physical and mental health show strong associations with health-related behavior. University students are one of the at-risk groups who are in a vulnerable transition phase from adolescence to adulthood, significantly affecting their health-related lifestyle. This study aims to identify different groups of university students with homogeneous health-related behavior, considering their dietary habits, physical activity, alcohol and tobacco consumption, mental well-being and lifestyle change motives. For data collection, an anonymous, closed-ended paper-and-pencil questionnaire was administered to a sample of 171 university students. Data analysis was performed using descriptive statistics, a t-test for independent samples, a chi-square test, Spearman correlation and hierarchical cluster analyses (Ward’s method, Dendrogram). On average, students reported good health (M = 4.84), including daily physical activity (M = 31.35 min) and regular consumption of fruits (M = 4.02) and vegetables (M = 4.19). The hierarchical cluster analysis revealed two distinct patterns among the students: “Caring for a healthy lifestyle” (N = 69) and “Physically inactive with poor mental well-being” (N = 62). Better health-related behavior was found among male students enrolled in higher study years (p ≤ 0.01). These findings provide new insights into the different patterns of health-related behavior among university students that require targeted health promotion actions. Universities should develop and implement courses in healthy lifestyles and sustain them in the curricula.